2021
DOI: 10.1097/cej.0000000000000701
|View full text |Cite
|
Sign up to set email alerts
|

Updated evidence-based recommendations for cervical cancer screening in France

Abstract: Introduction A national organized cytology-based cervical cancer screening program was launched in 2018 and rollout is ongoing. Concomitantly, the High Authority for Health (HAS) recently assessed new evidence on primary HPV testing to update screening recommendations. MethodsThe HAS commissioned systematic reviews and meta-analyses to evaluate the effectiveness of primary HPV screening; accuracy of HPV testing on self-samples; effectiveness of self-sampling to reach underscreened women; and triage strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…It is estimated that in 2020 there were 0.6 million new cases of cervical cancer and 0.34 million of deaths caused by this cancer. While the incidence and mortality of cervical cancer have been decreasing during the last several decade, this trend is mainly attributed to the widespread use of cervical screening [1,40]. However, the search for new chemical compounds that may inhibit the formation of this type of tumor is currently a priority in biomedical science.…”
Section: Activity Toward Cervix Uteri Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that in 2020 there were 0.6 million new cases of cervical cancer and 0.34 million of deaths caused by this cancer. While the incidence and mortality of cervical cancer have been decreasing during the last several decade, this trend is mainly attributed to the widespread use of cervical screening [1,40]. However, the search for new chemical compounds that may inhibit the formation of this type of tumor is currently a priority in biomedical science.…”
Section: Activity Toward Cervix Uteri Cancer Cellsmentioning
confidence: 99%
“…Recent studies have shown that FIS reduces the viability of HeLa cervical cancer cells (IC50 = 36 ± 0.5 µM) [40] and inhibits cell invasion and migration in a concentrationdependent manner. Additionally, cells of other lines, including SiHa and CaSki treated with FIS, show a decrease in mobility [24].…”
Section: Activity Toward Cervix Uteri Cancer Cellsmentioning
confidence: 99%
“…With internet service, women can participate in CCS at home or at facilities nearby, without the need to travel a distance to find medical services and to spend time simply to wait for sampling, which, together with the lack of need for a doctor's involvement in the sampling, is obviously cost-effective. Self-sampling-based HPV testing can increase participation and therefore increase the coverage of CCS (11)(12)(13)(14). In addition, privacy protection and the convenience of selfsampling will also encourage office workers to participate in the screening program.…”
Section: Feasibility and Acceptability Of Self-samplingmentioning
confidence: 99%
“…Since then, multiple studies have demonstrated that selfcollected samples work as well as provider-collected samples when tested on polymerase chain reaction (PCR) based HPV testing (12)(13)(14). And it could remarkedly expand screening coverage in both urban and rural areas, since it is far less reliant on medical resources (11)(12)(13). Several preliminary research projects in China (8, [14][15][16] has verified that selfsampling offers possibility to make CCS reach under or non-screened women.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation